2021
DOI: 10.3389/fpls.2021.717643
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Phyllosphere Bacterial Communities and Metabolomes in Newly Developed Needles of Cunninghamia lanceolata (Lamb.) Hook. at Four Stages of Stand Growth

Abstract: Host-plant-associated bacteria affect the growth, vigor, and nutrient availability of the host plant. However, phyllosphere bacteria have received less research attention and their functions remain elusive, especially in forest ecosystems. In this study, we collected newly developed needles from sapling (age 5 years), juvenile (15 years), mature (25 years), and overmature (35 years) stands of Chinese fir [Cunninghamia lanceolata (Lamb.) Hook]. We analyzed changes in phyllosphere bacterial communities, their fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 102 publications
2
1
0
Order By: Relevance
“…An observation confirmed that Bacillus in tomato leaf microbiota caused systematic exudation of acylsugar secondary metabolites in tomatoes (Korenblum et al, 2020). Some bacterial communities in the leaf layer of Cunninghamia lanceolata were closely related to some types of leaf metabolites, such as alkaloids, aldehydes, vitamins, azoles, and phenols, as reported by Sun et al (2021). In this study, we found that Hbc-6 mediated the significant correlation between some beneficial bacteria and metabolites under both normal and drought stress conditions (Figure 6).…”
Section: Physiological and Metabolic Response Mechanism Of Maize To H...supporting
confidence: 77%
See 1 more Smart Citation
“…An observation confirmed that Bacillus in tomato leaf microbiota caused systematic exudation of acylsugar secondary metabolites in tomatoes (Korenblum et al, 2020). Some bacterial communities in the leaf layer of Cunninghamia lanceolata were closely related to some types of leaf metabolites, such as alkaloids, aldehydes, vitamins, azoles, and phenols, as reported by Sun et al (2021). In this study, we found that Hbc-6 mediated the significant correlation between some beneficial bacteria and metabolites under both normal and drought stress conditions (Figure 6).…”
Section: Physiological and Metabolic Response Mechanism Of Maize To H...supporting
confidence: 77%
“…Recent studies have focused on the interaction between plant-related microorganisms and plant secondary metabolites ( Korenblum et al., 2020 ; Sun et al., 2021 ; Xia et al., 2021 ). An observation confirmed that Bacillus in tomato leaf microbiota caused systematic exudation of acylsugar secondary metabolites in tomatoes ( Korenblum et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of gene clusters of secondary metabolites and type VI gene clusters in Duganella species, many of which have antifungal properties, and the production of violacein, a major antibiotic, has been also established in many studies ( 132 135 ). The association of endophytic Duganella with secondary metabolites such as alkaloids and others has previously been also observed in Chinese fir ( 136 ). Bradyrhizobium is an Alphaproteobacteria that can undergo nitrogen-fixation symbiosis in the roots of many crops ( 137 ) found to contain gene clusters responsible for the biosynthesis of terpenes ( 138 ), phenolic compounds such as coumestrol ( 139 ), and alkaloids such as monocrotaline ( 140 ), linking their role in the production of secondary metabolites usually produced by the host.…”
Section: Discussionsupporting
confidence: 53%